2010
DOI: 10.1007/s00442-010-1721-2
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium excess reveals diurnal sources of water vapor in forest air

Abstract: An understanding of atmospheric water vapor content and its isotopic composition is important if we are to be able to model future water vapor dynamics and their potential feedback on future climate change. Here we present diurnal and vertical patterns of water isotope ratios in forest air (δ(2)H(v) and δ(18)O(v)) not observed previously. Water vapor observed at three heights over 3 consecutive days in a coniferous forest in the Pacific Northwest of the United States, shows a stratified nocturnal structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
78
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 50 publications
7
78
3
Order By: Relevance
“…6). The same trends were also found in urban settings (New Haven and Beijing), agricultural settings (Rosemount and Luancheng), forest (Borden Forest) and grassland (Duolun) (Welp et al, 2012), at one Beijing site (Wen et al, 2010), and in the Pacific Northwest (Lai and Ehleringer, 2011). These results showed that d moisture diurnal variation is not a pattern unique to any particular location or vegetation type, and the diurnal pattern of d moisture may suggest that d moisture is not a conserved tracer of humidity conditions in the marine moisture source region (Welp et al, 2012), and is strongly controlled by local evaporation and transpiration.…”
Section: Variations In D-excess In Air Moisture Near the Ground And Asupporting
confidence: 69%
See 3 more Smart Citations
“…6). The same trends were also found in urban settings (New Haven and Beijing), agricultural settings (Rosemount and Luancheng), forest (Borden Forest) and grassland (Duolun) (Welp et al, 2012), at one Beijing site (Wen et al, 2010), and in the Pacific Northwest (Lai and Ehleringer, 2011). These results showed that d moisture diurnal variation is not a pattern unique to any particular location or vegetation type, and the diurnal pattern of d moisture may suggest that d moisture is not a conserved tracer of humidity conditions in the marine moisture source region (Welp et al, 2012), and is strongly controlled by local evaporation and transpiration.…”
Section: Variations In D-excess In Air Moisture Near the Ground And Asupporting
confidence: 69%
“…The lowest d moisture values are found near the ground (1.5 ‰) at high altitudes during September (S1-Sep). The low values may be related to the atmospheric entrainment contribution, as atmospheric entrainment has been found to be responsible for the low d-excess values observed in the Pacific Northwest (Lai and Ehleringer, 2011). In our study, during the sunny days, the d moisture values vary diurnally, showing a clear and robust pattern of the highest d moisture values at midday, and the lowest d moisture values at night at all the sites (Fig.…”
Section: Variations In D-excess In Air Moisture Near the Ground And Asupporting
confidence: 55%
See 2 more Smart Citations
“…In addition, there is a need for dual tracer databases, in order to use the deuterium excess signal (d = δD − 8 × δ 18 O; Dansgaard, 1964) as an additional indicator of atmospheric processes. Indeed, d is often considered as a indicator of evaporation conditions, but its interpretation in continental vapour remains complex since it is affected by the multiple vapour sources, combining the initial oceanic vapour and evapotranspiration from different continental water sources (Gat et Matsui, 1991;Vallet-Coulomb et al, 2008;Lai and Ehleringer, 2011;Welp et al, 2012;Jouzel et al, 2013;Aemisseger et al, 2014).…”
Section: Introductionmentioning
confidence: 99%